Upaya Negara Korea Selatan dalam Menangani Food Waste (Sampah Makanan) - Wulandari, Nadia (Program Studi Magister Manajemen Lingkungan, 2023)
Food waste and food loss are environmental issues which are frequently discussed around the world, as well as the growth of food that does not exhaust both in houses and restaurants. This issues is included in point 12 of SDGs regarding ensure sustainable consumption and production patterns. The purpose of this research is to identify South Korea’s efforts and barriers to addressing these issues. The concept used is food waste management. This research methods is qualitative with literature and internet-based research. The result of this research show that by implementation of a volume-based waste fee policy and a pay as you throw system as well as the contribution of the Korea Zero Waste Movement and South Korea’s state has increased in the minimization of food wastw production and there has been an increase in recycling, although there are still some barriers to food wastage.